1998
DOI: 10.1128/aem.64.2.496-503.1998
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of a Bacterial Consortium Reductively Dechlorinating 1,2,3- and 1,2,4-Trichlorobenzene

Abstract: A bacterial mixed culture reductively dechlorinating trichlorobenzenes was established in a defined, synthetic mineral medium without any complex additions and with pyruvate as the carbon and energy source. The culture was maintained over 39 consecutive transfers of small inocula into fresh media, enriching the dechlorinating activity. In situ probing with fluorescence-labeled rRNA-targeted oligonucleotide probes revealed that two major subpopulations within the microbial consortium were phylogenetically affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Cells were concentrated by centrifugation (8000× g , 25 min, Sorvall RC‐5B centrifuge, Sorvall, Bad Homburg, Germany) and subsequently enriched in bicarbonate‐buffered, sulfide‐reduced mineral medium [21], supplemented with lactate (10 mM), ethanol (10 mM), benzoate (5 mM), acetate (20 mM) or propionate (10 mM), with sulfate (20 mM) as the electron acceptor. Medium preparation was performed according to Adrian et al [22]. After growth and production of sulfide, bacteria from enrichment cultures with lactate and ethanol were isolated by use of deep agar dilution series [21].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were concentrated by centrifugation (8000× g , 25 min, Sorvall RC‐5B centrifuge, Sorvall, Bad Homburg, Germany) and subsequently enriched in bicarbonate‐buffered, sulfide‐reduced mineral medium [21], supplemented with lactate (10 mM), ethanol (10 mM), benzoate (5 mM), acetate (20 mM) or propionate (10 mM), with sulfate (20 mM) as the electron acceptor. Medium preparation was performed according to Adrian et al [22]. After growth and production of sulfide, bacteria from enrichment cultures with lactate and ethanol were isolated by use of deep agar dilution series [21].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the strict screening criteria used in this study, the data set of rate constants was relatively small, consisting of rate constants from six separately published studies [3,[6][7][8][9][10][11][12][13]. The majority of the rate constants in the data set came from a single study [6][7][8] in which biotransformation rates were reported for a large number of chlorinated aromatic compounds in slurries containing sediment from an estuary in Japan.…”
Section: Approachmentioning
confidence: 99%
“…2. Comparison of calculated versus observed rate constants (d Ϫ1 ) for the external validation data set [3,[9][10][11][12][13]. Calculated rate constants were evaluated using QSAR2.…”
Section: Multiple Regression Analysis and Qsar Developmentmentioning
confidence: 99%
“…Cells were concentrated by centrifugation (8000Ug, 25 min, Sorvall RC-5B centrifuge, Sorvall, Bad Homburg, Germany) and subsequently enriched in bicarbonate-bu¡ered, sul¢de-reduced mineral medium [21], supplemented with lactate (10 mM), ethanol (10 mM), benzoate (5 mM), acetate (20 mM) or propionate (10 mM), with sulfate (20 mM) as the electron acceptor. Medium preparation was performed according to Adrian et al [22]. After growth and production of sul-¢de, bacteria from enrichment cultures with lactate and ethanol were isolated by use of deep agar dilution series [21].…”
Section: Source Of Organisms and Cultivation Conditionsmentioning
confidence: 99%